Induction of Callose Deposition in Tobacco (Nicotiana tabacum) by Bacterial Lipopolysaccharide Pseudomonas syringae pv. tabaci and Pseudomonas syringae pv. Glycinea - Marianingsih, Pipit; Salamah, Andi; Ichinose, Yuki (UI Scholars Hub, 2014)
Lipopolysaccharide (LPS) is a major component of outer-membrane gram-negative bacteria, and it can act as a Pathogen-Associated Molecular Pattern (PAMP) for perception of pathogens by plants. LPS can be recognized by plants, triggering certain plant defense-related responses, including callose deposition. This study investigated induction of callose deposition by bacterial LPS in tobacco. Tobacco leaves were infiltrated with 400 µg/mL and 800 µg/mL LPS extracted from Pseudomonas syringae pv. tabaci (Pta) and Pseudomonas syringae pv. glycinea (Pgl) and incubated for 24 h or 48 h. To detect callose deposition, tobacco leaves were cleared in lactophenol solution, stained with aniline blue, and visualized by fluorescence microscopy. Results showed that LPS from Pgl induced more callose deposition in tobacco leaves than did that from Pta. In addition, a Pearson correlation test revealed that incubation period was the most significant factor in callose deposition, followed by the type of LPS bacteria. However, LPS concentration was not significantly corelated to callose deposition in tobacco leaves